ASPEK - ASPEK YANG BERPENGARUH TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA - Risnawati, Heni; Mudiarti, Hasna; Muttaqin, Ibnu (Universitas Wahid Hasyim, 2024)
The aim of this research is to analyze the influence of entrepreneurial knowledge, family environment and freedom to work on students' interest in entrepreneurship at Pancasakti University, Tegal. The research method used is quantitative research. The sampling technique was purposive sampling which had the criteria of UPS Tegal accounting students who had taken entrepreneurship courses. Data collection using a G-Form questionnaire distributed to students. The research results simultaneously show that entrepreneurial knowledge, family environment and freedom to work influence students' entrepreneurial interest. Partially, entrepreneurial knowledge has a significant effect on entrepreneurial interest. The family environment has a significant influence on students' entrepreneurial interest. Freedom to work has a significant effect on students' entrepreneurial interest.Â Keywords; Entrepreneurship knowledge, Family environment, Freedom in entrepreneurship, Interest in entrepreneurship